Does say-on-pay benefit shareholders?. (28th May 2021) - Vithayathil, Joseph; Shivendu, Shivendu
We develop a conceptual, game theoretic model to analyse say-on-pay and understand whether it benefits shareholders. We analyse the traditional delegated-governance structure wherein shareholders delegate CEO compensation decision to the board. The board has an informational advantage and can collude with management for private benefits. We contrast this with an alternate governance structure referred to as owner-governance where shareholders determine compensation. Firm performance is dependent on CEO effort and stochastic factors. There are clear insights for policy. First, contrary to popular sentiment, say-on-pay does not improve shareholder welfare. Second, incentives for the CEO decrease shareholder welfare for the most part, because luck is a major factor. Third, shareholders are better off trading say-on-pay for the right to fire board members by dismantling board entrenchment, enabled by widely adopted staggered boards and poison pills. Entrenchment makes it prohibitively costly to remove and replace boards or a majority of board members.